Pomorska politika Evropske zajednice - Ivović, Jovo (Promet - Traffic&Transportation, 2012)
The paper deals with the significance of maritime transport for the EC member ’states and furnishes the data on capacities i.e. the fleet of cessels of the EC quoting a series of unilateral acts and bilateral treates on booking of cargo to subsequently review the policy ill shipping trade and institution of the European Register. The author then analyses the fiscal policy in shipping in the EC and mutual cooperation within this scope in the EC. The author any thinks that the shipping trade ill Yugoslavia would not experience any negative affects due to the innovations in the shipping policy of the EC.